Analysis of textured journal bearing with slip boundary condition and pseudoplastic lubricants. (15th August 2022) - Arif, Mohammad; Kango, Saurabh; Shukla, Dinesh Kumar
Highlights: Effect of Pseudoplastic lubricants, slip boundary condition, and geometrical shape of micro-texture is observed on the performance of hydrodynamic journal bearings. Mass conserving Reynolds equation with considering slip, texture, and lubricant rheology has been solved. Influence of lubricant viscosity loss with temperature rise is also considered. Steady-state performance characteristics of conventional and slip-texture bearing are compared. Slip-texture with suitable selection of lubricant rheology is beneficial in increasing the scope of liquid lubricants in the small-scale hydrodynamic journal bearings. Abstract: The present study investigates the combined influence of slip boundary condition and non-Newtonian lubricants on the tribological performance of hydrodynamic textured journal bearing. To accurately predict the effect of air/vapor bubble formation in diverging zone of the slip-texture bearing, the modified Reynolds equation with considering the Elrod cavitation model has been solved. In addition, the energy equation under adiabatic condition has been also solved for including the loss of viscosity with the temperature rise of lubricant. It has been observed that slip-texture bearings with change in rheology of lubricant from Newtonian to Pseudoplastic shows significant improvement in the maximum pressure, the average rise in temperature, and lubricant-bearing friction-force. Further findings of the study indicate that the combined effect of slip boundary condition and micro-texture with suitable selection of lubricant rheology is beneficial in increasing the stability of hydrodynamic lubricant film in the journal bearings. Graphical abstract: Image, graphical abstract